Unilateral Tax Reform: Border Adjusted Taxes, Cash Flow Taxes, and Transfer Pricing - Eric Bond; Thomas A. Gresik (Center for Economic Studies and ifo Institute (CESifo), 2018)
We study the economic effects of unilateral adoption of corporate tax policies that include destination-based taxes and/or cash ow taxes in a heterogeneous agent model in which multinational firms can endogenously shift income between countries using transfer prices. Standard pass through arguments no longer apply because of the income shifting behavior of multinationals. Over or under- pass through will affect domestic consumer prices charged by multinational firms and will distort the decision of international businesses to outsource intermediate goods or to produce them in a foreign subsidiary. The welfare of the adopting country can decrease both with the adoption of destination-based taxes and the adoption of cash ow taxes. For a country with sufficiently large export markets that can optimally adjust its corporate tax rate on domestic earnings, unilaterally adopting cash ow taxation with full destination-based rate adjustments will reduce welfare.
Keywords: F23; H21; H25; H26; 330; border adjustments; destination-based taxes; source-based taxes; cash flow taxes; income taxes; transfer pricing; unilateral tax reform